Large and Small Lead and Zinc Miners Reach Unanimity On SLIDING SCALE IMPORT TAX (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1953)
FOR two days preceding the Colorado Mining Association annual meeting, officers representing all interests of the lead and zinc producers hammered away at remedies for the ills of the industry behind closed doors at the University Club in Denver. For once in the stormy history of the industry, large and small producers alike came to agreement with an automatic sliding scale stabilization import tax. The proposal set forth in full on the following page, is not new being merely an amplification of the tariff arrangement whereby tariffs are imposed when the price drops below ceiling. Its advocates claim that it is simple, automatic, and flexible. It will give stability to the industry without subsidies and since no government bureaus will be required to administer it, there will be no cost to the taxpayer.